W(x) = x¹⁰ - 1 P(x) = - x² = x( 1 - x)
x (1 - x) = 0
x = 0 ∨ x = 1
W ( 0) = R(0)
W ( 1) = R(1)
W(0) = 0¹⁰ - 1 = - 1
W(1) = 1¹⁰ - 1 = 1 - 1 = 0
R(x) = ax + b
R(0) = a ·0 + b = b
R(1) = a ·1 + b = a + b
b = - 1
a + b = 0
a - 1 = 0
a = 1
R (x) = x - 1
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
W(x) = x¹⁰ - 1 P(x) = - x² = x( 1 - x)
x (1 - x) = 0
x = 0 ∨ x = 1
W ( 0) = R(0)
W ( 1) = R(1)
W(0) = 0¹⁰ - 1 = - 1
W(1) = 1¹⁰ - 1 = 1 - 1 = 0
R(x) = ax + b
R(0) = a ·0 + b = b
R(1) = a ·1 + b = a + b
b = - 1
a + b = 0
a - 1 = 0
a = 1
R (x) = x - 1